Diagnostic Accuracy of the Madras Head Injury Prognostication Scale (MHIPS) in Predicting Mortality among Traumatic Brain Injury Patients - Y., Nikhil Reddy; J., Devendra Prasad K.; R., Krishna Moorthy D. G. S.; K., Rajesh; R., Aravind S. (Asian Journal of Neurosurgery, 2025)
Accurate prediction of outcomes in traumatic brain injury (TBI) is crucial for optimizing therapeutic interventions and improving patient survival rates.This article determines the diagnostic accuracy of Madras Head Injury Prognostication Scale (MHIPS) in predicting mortality among patients with TBI, and compares the performance of MHIPS scores with that of Corticosteroid Randomisation after Significant Head Injury (CRASH) and International Mission for Prognosis and Analysis of Clinical Trials (IMPACT) scores.This was a prospective observational study conducted among patients (n = 100) with clinical evidence of TBI presenting to the Department of Emergency Medicine, R. L. Jalappa Hospital and Research Centre, Tamaka, Karnataka, India, between August 2023 and July 2024.Of the 100 patients, 92 patients (92.0%) were survivors of which 4 patients (4.0%) had disability and 8 patients died/nonsurvivors (8.0%). Age more than 40 years, higher heart rate, lower Glasgow Coma Scale scores, lower MHIPS scores, higher CRASH scores, and higher IMPACT scores were significantly (p < 0.05) associated with mortality among patients with TBI. However, gender, mode of injury, diagnosis, time to presentation, systolic blood pressure (BP), diastolic BP, and respiratory rate did not vary significantly between nonsurvivors and survivors in the present study (p > 0.05). The mean (standard deviation) duration of ventilation among nonsurvivors was 3.3 (2.2), and that among survivors was 0.5 (1.1)—the difference was statistically significant (p < 0.05). The area under the curve of MHIPS scores was 0.912, in comparison with 0.893 for CRASH scores and 0.927 for IMPACT scores (p < 0.05). The MHIPS scores, with a cutoff of 13.5, showed a sensitivity of 87.5%, specificity of 81.5%, positive predictive value (PPV) of 29.2%, and negative predictive value (NPV) of 98.7%. The CRASH scores, with a cutoff of 5.5, demonstrated a sensitivity of 87.5%, specificity of 53.3%, PPV of 14.0%, and NPV of 98.0%. The IMPACT scores, with a cutoff of 8.5, had a sensitivity of 87.5%, specificity of 91.3%, PPV of 46.7%, and NPV of 98.8%. All three scoring systems showed statistically significant predictive accuracy.MHIPS, CRASH, and IMPACT are effective tools for prognosticating mortality in TBI patients. MHIPS score offers simplicity and ease of use, making it valuable in resource-limited environments.
Keywords: Corticosteroid Randomisation after Significant Head Injury (CRASH); diagnostic accuracy; International Mission for Prognosis and Analysis of Clinical Trials (IMPACT); Madras Head Injury Prognostication Scale (MHIPS); traumatic brain injury (TBI)